SURGICAL ANATOMY OF KURPARA MARMA WITH SPECIAL REFERENCE TO ELBOW JOINT INJURY - Geethakumar (International Journal of Applied Ayurved Research, 2016)
Marma is constituted by confluence of Mamsa (muscle), Sira (vessels), Snayu (nerve, tendon, ligament), Asthi(bone), snadhi (joints).This five tissue participate to play vital role in prognosis of traumatic result. kurpara marma is one of the Vaikayalkara marma (loss of function). Kurpara marma or kurpara sandhi marma includes the proximal radiounlnar and the joint between humarus, and radioulnar. An injury to this marma causes deformity, pain and swelling. The articulation of elbow joint occurs between the trochlea and capitulum of humerus and trochlear notch of the ulna and head of radius. The elbow is capable of simple hinge movement of flexion and extension injury oriented deformity at elbow joint. Such injuries causes dislocation, sublaxation, sprain, instability, leading to severe pain stiffness and deformity. Injuries can be avoided by certain preventive measures.